Support to Government of India for Implementation of National Urban Sanitation Policy - World Bank (Washington, DC, 2015)
This synthesis report details the process, outputs and intermediate outcomes of the World Bank’s Water and Sanitation Program (WSP) Technical Assistance (TA) to Support Government of India for implementation of the National Urban Sanitation Policy (P131963). The objective of this TA was to (i) strengthen urban sanitation services and target the urban poor by development of strategies for regulation, funds allocation, improved accountability mechanisms and implementation of inclusive sanitation policies at national level and in at least five states, with two of these low-income states (LIS). This was to be supplemented with (ii) enabling design and use of improved performance monitoring systems by Government of India, 3 states and 300 urban local bodies by 2015, and (iii) strengthen capacity of local urban government institutions to provide improved – inclusive and sustainable – sanitation services for all. This TA provides the building blocks for sustainable sanitation improvements which are being adopted and implemented as part of another TA (P131967) in Madhya Pradesh and Tripura to pilot and operationalize City Sanitation Plans (CSPs) towards outcome oriented sector improvements. The areas addressed in this TA include the following specific goals of the NUSP: open defecation free cities, and integrated city-wide sanitation. The TA provided assistance to central government and the states in putting in place various elements identified as necessary for sector improvement, including planning, provisioning and monitoring processes. The TA also identified the need for the cities to see opportunities for financial recovery of investments through reuse and recycle strategies, to strengthen the incentive for investment in sanitation improvements.